2023
DOI: 10.3892/mi.2023.71
|View full text |Cite
|
Sign up to set email alerts
|

The combination of positive anti‑WDR1 antibodies with negative anti‑CFL1 antibodies in serum is a poor prognostic factor for patients with esophageal carcinoma

Abstract: WD repeat-containing protein 1 (WDR1) regulates the cofilin 1 (CFL1) activity, promotes cytoskeleton remodeling, and thus, facilitates cell migration and invasion. A previous study reported that autoantibodies against CFL1 and β-actin were useful biomarkers for diagnosing and predicting the prognosis of patients with esophageal carcinoma. Therefore, the present study aimed to evaluate the serum levels of anti-WDR1 antibodies (s-WDR1-Abs) combined with serum levels of anti-CFL1 antibodies (s-CFL1-Abs) in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our findings highlighted potential biomarkers for stroke including DIDO1, CPSF2, FOXJ2, DNAJC2, ALDOA, FH4, ASXL2, AP3D1, SERPINE1, and TSTD2 [11][12][13][14][15][16][17]. Likewise, we identified LRPAP1, CFL1, WDR1, and striatin 4 as potential markers for digestive tract tumors [18][19][20][21].…”
Section: Introductionsupporting
confidence: 55%
“…Our findings highlighted potential biomarkers for stroke including DIDO1, CPSF2, FOXJ2, DNAJC2, ALDOA, FH4, ASXL2, AP3D1, SERPINE1, and TSTD2 [11][12][13][14][15][16][17]. Likewise, we identified LRPAP1, CFL1, WDR1, and striatin 4 as potential markers for digestive tract tumors [18][19][20][21].…”
Section: Introductionsupporting
confidence: 55%
“…Our SEREX screening method has identified many antibody biomarkers or antigens, including trophoblast cell surface antigen 2 (TROP2), 6 solute carrier family 2 member 1/glucose transporter 1 (SLC2A1/GLUT1), 7 ZIC2, 8 BAMBI, 9 striatin, 10 LDL receptor-related protein-associated protein 1, 11 proprotein convertase subtilisin/kexin type 9, 12 cofilin, 13 and WD repeat-containing protein 1. 14 In the present study, SEREX screening for esophageal carcinoma identified the SKI proto-oncogene protein and transmembrane p24 trafficking protein 5 (TMED5). The serum anti-SKI antibody (s-SKI-Ab) and anti-TMED5 antibody (s-TMED5-Ab) levels were compared between patients with esophageal carcinoma and healthy donors (HDs).…”
Section: Introductionmentioning
confidence: 82%
“…The sequencing of isolated cDNA clones makes SEREX suitable for large‐scale screening of tumor antigens. Our SEREX screening method has identified many antibody biomarkers or antigens, including trophoblast cell surface antigen 2 (TROP2), 6 solute carrier family 2 member 1/glucose transporter 1 (SLC2A1/GLUT1), 7 ZIC2, 8 BAMBI, 9 striatin, 10 LDL receptor‐related protein‐associated protein 1, 11 proprotein convertase subtilisin/kexin type 9, 12 cofilin, 13 and WD repeat‐containing protein 1 14 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the antibody levels in serum samples from patients with CVD obtained from Chiba University Hospital were examined. Given that OSAS is related to atherosclerosis and is associated with a high risk of AIS and CVD (36)(37)(38)(39), the present study also examined the sera of patients with OSAS obtained from Chiba University Hospital. Compared with those of the HDs, the s-KIAA0513-Ab levels were significantly higher in the patients with CVD or OSAS (Fig.…”
Section: Elevation Of Serum Antibody Levels Against Kiaa0513mentioning
confidence: 99%
“…The anti-p53 antibody is a typical antibody biomarker for cancer that has been used in clinical practical for diagnosing, monitoring and predicting the prognosis of esophageal cancer (EC) and head and neck cancer ( 26 , 27 ). Further application of the serological identification of antigens by cDNA expression cloning and the protein array method have identified autoantibodies against tumor-associated calcium signal transducer 2( 28 ), solute carrier family 2/facilitated glucose transporter, member 1( 29 ), tripartite motif-containing 21( 30 ), myomegalin ( 31 ), makorin 1( 32 ), esophageal carcinoma SEREX antigen ( 33 ), cyclin L2( 34 ), cofilin, β-actin ( 35 ) and WD repeat-containing protein 1( 36 ) for EC; FBP-interacting repressor for colorectal cancer (CRC) ( 37 ) and gastric cancer (GC) ( 38 ); SH3 domain, GRB2-like 1( 39 ) and filamin C ( 40 ) for glioma; EP300-interacting inhibitor of differentiation 3 for non-functional pancreatic neuroendocrine tumors ( 41 ); wingless-type MMTV integration site family, member 7 for biliary cancer ( 42 ); and coatomer protein complex subunit epsilon ( 43 ), differential screening-selected gene aberrant in neuroblastoma ( 44 ), and sorting nexins 16( 45 ) for obstructive sleep apnea syndrome (OSAS). Here, we report on serum antibodies against KIAA0513 (s-KIAA0513-Ab) as a broad-spectrum biomarker applicable to atherosclerosis-related diseases such as ischemic stroke, cardiovascular disease (CVD), chronic kidney disease (CKD), DM and solid cancers.…”
Section: Introductionmentioning
confidence: 99%